Assessment of present status and action plan development of vegetable seed enterprise in Rukum, Nepal - Pun, Amar Bahadur; Poudyal, Damodar (Journal of Agriculture and Natural Resources, 2018)
Vegetable seed enterprise is a highly potential sub-sector for the economic growth of rural farmers in Nepal. Rukum has been known as the most important district for vegetable seed production since long time because of favorable agro-climatic condition. However, Rukums' sub-sector is facing several limitations including organized production and marketing, technology adoption and entrepreneurship development. This study has been carried out to assess the vegetable seed sub-sector of Rukum and propose action plans accordingly for the sustainable seed enterprise development. The study conducted stakeholder workshop and field survey; consulted district line agencies, seed producers and cooperatives, agro-vets and seed companies, and reviewed previous works. The study found that there were many individual farmers, farmers' groups and cooperatives being involved in vegetable seed production in the district. The role of private sector is emerging rapidly with higher share in the seed marketing. The public sector is still a major player for conducting research; and provision of source seeds, quality assurance and other support services. Strategic efforts and action plans are needed to push the existing traditional seed sub-sector towards commercial venture. Technology adoption for quality seed production, processing and marketing; transformation of the classical seed sub-sector into a competitive and sustainable enterprise; organized and demand led seed production programs; and coordination and participatory approaches among stakeholders in seed value chain activities are highly recommended.